Understanding Repurchase Decision of Boba Milk Drink among Gen Z in Jakarta - Indrawan, Umar; Wismiarsi, Tri; Hatta, Holila (Journal of Business & Applied Management, 2025)
The growth of boba milk drinks in Greater Jakarta has led to tight competition in the market. Regarding that, numerous small new brands exist in the market. As a result, the big company in the boba milk drink industry has a threat of losing its competition in the market. This study aims to examine consumers’ behavior to repurchase boba milk drinks by implementing TPB attitude, subjective norm, perceived behavioral control, product quality, and E-WOM towards repurchasing intention for boba milk drinks. Using the online survey, the data were collected from 165 respondents in greater Jakarta who love to drink boba milk. The findings indicate that attitudes are the strongest predictor of repurchasing intention for boba milk drink. Besides, the findings of this study showed that E-WOM is also known to have an influence on subjective norms, but E-WOM and subjective norms do not have a significant impact on repurchasing intention. Meanwhile, the findings show that perceived behavioral control has a significant impact on repurchasing intention.